Entonación de los enunciados aseverativos en el español de Tuxtla Gutiérrez, Chiapas - Méndoza Vázquez, Érika (El Colegio de México, 2018)
The main objective of this paper is to describe the tonal configurations of the assertive statements in the Spanish of Tuxtla Gutiérrez, Chiapas. The analysis integrates three data sources: formal, semi-spontaneous and spontaneous. The findings show: i)the nuclear pitch accent L+(¡)H*, favoured by men and by the spontaneous style, and ii)the early alignment of the first tonal peak, favoured by the adult age group and those with a low level of instruction. By offering a sociolinguistic and geolinguistic description of this variety this paper seeks to provide new data in the field of prosodic dialectology in Mexico.